1956
DOI: 10.1002/jsfa.2740070113
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen cycle in grassland soils

Abstract: We now have a fairly complete picture of the nitrogen cycle in grassland soils and the relevant features are discussed.The large amounts of nitrogen needed to obtain high production from pastures are derived initially almost entirely from nitrogen-fixation by clovers in New Zealand, where under some of the better conditions clovers may fix about 600 lb. of nitrogen per acre per year. The associated grasses derive their nitrogen from soil organic matter, underground transference from clovers, and from excreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1960
1960
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…While these data represent a single measurement in time, they are consistent with past studies that have demonstrated that nitrate and ammonium levels in unfertilized grassland soils are almost universally very low (Richardson 1938, Walker 1956, Woodmansee et al 1978). Nitrate-N concentrations were consistently Ͻ1 mg/kg in the soil profile, while NH 4 -N concentration were Ͻ5 mg/kg.…”
Section: Soil Responsesupporting
confidence: 89%
See 1 more Smart Citation
“…While these data represent a single measurement in time, they are consistent with past studies that have demonstrated that nitrate and ammonium levels in unfertilized grassland soils are almost universally very low (Richardson 1938, Walker 1956, Woodmansee et al 1978). Nitrate-N concentrations were consistently Ͻ1 mg/kg in the soil profile, while NH 4 -N concentration were Ͻ5 mg/kg.…”
Section: Soil Responsesupporting
confidence: 89%
“…Nitrate-N concentrations were consistently Ͻ1 mg/kg in the soil profile, while NH 4 -N concentration were Ͻ5 mg/kg. While these data represent a single measurement in time, they are consistent with past studies that have demonstrated that nitrate and ammonium levels in unfertilized grassland soils are almost universally very low (Richardson 1938, Walker 1956, Woodmansee et al 1978).…”
Section: Soil Responsesupporting
confidence: 89%
“…Since the 15N content of the grass in the mixture is lower than that of the grass monoculture, it seems likely that the additional source of N is at, or near, natural abundance (0.366at.% and is derived from N fixed by the legume. This could involve direct transfer of N (Eaglesham, 1981;Haystead and Marriott, 1978;Ledgard et al, 1985;Ta and Faris, 1988), or indirect transfer via mineralisation of senescing clover roots and nodules (Haynes, 1986;Henzell, 1972;Walker, 1956). There is also evidence from 15N studies that N is released from the root-nodule system (Ruschel et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In studies on the nutrient economy of grasslands, Walker (1955Walker ( , 1956 has pointed out that under New Zealand conditions large accumulations of organic matter and organically bound nutrients are to be expected. It is generally recognised that mineralisation of organically bound nitrogen, phosphorus, and sulphur must take place to render them available to plants.…”
Section: Introductionmentioning
confidence: 99%